Porphyra haitanensis polysaccharide (PH) attenuates cell hyperplasia via remodeling the cross-talk between Hippo/YAP and mTOR pathways - Chong Wang; Wanglei Lin; Zhihua Sun; Yiming Sun; Yanbo Wang; Linglin Fu (Food Science and Human Wellness)
Porphyra polysaccharide is a special kind of nutrient showing multiple physiological functions including regulating cell proliferation, but the detailed mechanisms are not fully revealed, impairing its further development and applications. This work was to purify and characterize the Porphyra haitanensis polysaccharide (PH), investigate its physiological function, and demonstrate the underlying mechanisms. The purified PH was first characterized by Fourier-transform infrared spectroscopy. Then an intestinal epithelial cell model was established, in which PH significantly suppressed cell hyperplasia. Specifically, PH activated the Hippo/YAP pathway, which subsequently activated mTOR pathway, however mTOR activated Hippo in the absence of PH. Moreover, both the inhibition of Hippo by YAP1 knock-down and the suppression of mTOR by rapamycin impaired PH function. These results indicated that PH attenuated hyperplasia activity by remodeling the cross-talk between Hippo/YAP and mTOR pathways, which revealed potential targets and approaches for treating hyperplasia-related diseases and provided novel ways to utilize P. haitanensis as well as other related functional foods.